DEVELOPMENT OF USED ELECTRONICS E-COMMERCE MOBILE APPLICATION - MOHD KHAIRUDDIN, AMIR SYAHMI (IRC, 2020)
As the technologies and world economy continues to progress forward, an increasing number of older technologies are becoming more obsolete and being replaced with more sophisticated and innovative inventions. The problem arises when the world is unable to meet the demand needed for managing and handling the process of recycling the discarded old technologies which are known as e-wastes. This is because the current process of dismantling and recycling the e-waste is costly and can be damaging to the environment and human health. This study proposes a new method of curbing the generation of e-waste by reusing and reselling used electronics through a mobile application that focuses on the e-commerce of used electronics. Unlike the traditional method of handling e-waste which is relying on consumers to make the correct decision on selecting the right channel of e-waste recycling, the proposed method aims to prevent the used electronics from becoming e-waste in the first place. This study will discuss about the current flow of e-waste, the effects of e-wastes and the development of the mobile application. This study will also conduct research on the consumer perception on e-waste recycling and towards reusing second-hand electronics sold on e-commerce platforms.